2014
DOI: 10.1016/j.indcrop.2013.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Erica australis extract on Caco-2 cells, fibroblasts and selected pathogenic bacteria responsible for wound infection

Abstract: 25Plants from the genus Erica are used in many countries to treat several ailments. In this

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Within the tested concentrations, WOLE presented impact neither on the viability of HTB‐140 and WM793 melanoma cells, nor normal skin fibroblasts. Such results are consistent with our previous study where normal fibroblasts had been reported to have been less susceptible to plant extracts than cancer cell lines . The activity of the tested extract was however significantly lower in comparison to the standard cytotoxic drug used – mitoxantrone ( IC 50 2 – 5 and 0.2 – 0.45 μg/ml for cancer and normal cells, respectively) …”
Section: Resultssupporting
confidence: 92%
“…Within the tested concentrations, WOLE presented impact neither on the viability of HTB‐140 and WM793 melanoma cells, nor normal skin fibroblasts. Such results are consistent with our previous study where normal fibroblasts had been reported to have been less susceptible to plant extracts than cancer cell lines . The activity of the tested extract was however significantly lower in comparison to the standard cytotoxic drug used – mitoxantrone ( IC 50 2 – 5 and 0.2 – 0.45 μg/ml for cancer and normal cells, respectively) …”
Section: Resultssupporting
confidence: 92%
“…The optical density was measured at 570 nm (the reference wavelength was 630 nm) using a microplate reader (Tecan Austria GmbH, Grodig, Austria). Results were reported using the following formula: (average OD value of three measurements for each experimental group/average OD value of control group) Â 100% (Nunes et al 2014). …”
Section: Mtt Assaymentioning
confidence: 99%
“…Since ancient times, Erica species have been used as a traditional medicine for the treatment of burns and wounds by the local people in Anatolia. The studies have been showed that Erica species possess antiulcer [8,9], antimicrobial [10,11], antibacterial, cytotoxic [12][13][14][15] and antioxidant [16][17][18][19][20] activities. It has also been reported that Erica species have (poly) phenolic, flavonoid, coumarin and triterpenoid, compounds [21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%